Efficacy of the histamine 3 receptor (H3R) antagonist pitolisant (formerly known as tiprolisant; BF2.649) in epilepsy: Dose-dependent effects in the human photosensitivity model - Kasteleijn- Nolst Trenité, Dorothée; Parain, Dominique; Genton, Pierre; Masnou, Pascal; Schwartz, Jean-Charles; Hirsch, Edouard (Epilepsy & behavior, 2013)
A new class of drugs, the nonimidazole histamine 3 receptor (H3R) antagonists, has been developed in the past decade for treatment of various brain diseases. Pitolisant is such a drug. We studied the pharmacodynamic effect of pitolisant in patients with epilepsy in early Phase II, using the photosensitivity proof of concept model. A total of 14 adult patients (11 females and 3 males; 5 drug naïve) were studied for three days to evaluate the effect of a single oral dose of pitolisant on EEG photosensitivity ranges. All patients showed repeatedly a generalized photoparoxysmal response (PPR) prior to drug administration on placebo Day 1. A statistically significant suppressive effect (standardized photosensitive response [SPR] reduction as measured with paired t-tests) for 20-, 40-, or 60-mg doses of pitolisant was seen in 9/14 (64%) patients of whom 6/14 (43%) showed abolition of the response to intermittent photic stimulation (IPS). Patients on the highest dosage (60mg) showed the strongest effect with an effect lasting up to 28h. Thus, full-scale Phase II studies with this novel H3R antagonist, pitolisant, in patients with epilepsy are warranted. [Display omitted] •Pitolisant, a histamine 3 receptor antagonist, is effective in animal models of epilepsy.•Pitolisant reduced the photosensitivity range in 64% of photosensitive subjects.•Pitolisant abolished the photoparoxysmal response in 43% of subjects.•Pitolisant effect was significant from 2-6 hours after dose.